2000
DOI: 10.1037/0893-164x.14.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of attrition from cessation treatment in smokers with a history of major depressive disorder.

Abstract: Attrition from smoking cessation treatment by individuals with a history of major depression was investigated. An investigation of preinclusion attrition examined differences between eligible smokers who did (n = 258) and did not (n = 100) attend an initial assessment session. Postinclusion attrition was investigated by comparing early dropouts (n = 33), lale dropouts (n = 27), and treatment completers (n = 117). Those who failed to attend the assessment session were more likely to be female, to smoke cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 32 publications
6
57
4
Order By: Relevance
“…At the end of the one-year follow-up, the abstinence rates were 9.8%, 12.5% and 5.9%, respectively. Over the past several years, researchers have observed that the remaining smokers in the population are primarily heavily addicted, long-term users (Curtin, Brown, & Sales, 2000;Hughes & Brennan, 1996), who are resistant to current treatments (Irvin & Brandon, 2000;Irvin, Hendricks & Brandon, 2003). The rates of relapse in our study appeared to follow the same trend that these researchers have described.…”
Section: Discussionsupporting
confidence: 76%
“…At the end of the one-year follow-up, the abstinence rates were 9.8%, 12.5% and 5.9%, respectively. Over the past several years, researchers have observed that the remaining smokers in the population are primarily heavily addicted, long-term users (Curtin, Brown, & Sales, 2000;Hughes & Brennan, 1996), who are resistant to current treatments (Irvin & Brandon, 2000;Irvin, Hendricks & Brandon, 2003). The rates of relapse in our study appeared to follow the same trend that these researchers have described.…”
Section: Discussionsupporting
confidence: 76%
“…A more recent randomized multicenter trial that matched treatment protocol with particular patient types found much lower attrition rates, with 87% of participants attending a three-year follow-up evaluation [2]. Regarding smoking cessation, older, heavier smokers were more likely to participate but less likely to abstain [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some predictors of attendance at follow-up evaluations have emerged in the literature, but again, there is a lack of consistency, in part, due to the extreme heterogeneity of participants across studies. Predictors of increased attrition include previous treatment for psychiatric or emotional problems, slower initiation of participant into a treatment program after randomization [2], depressed mood [3,4], and failure to complete at least one treatment session [5]. Attrition appears lowest when the research area is of personal interest to participants [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is unclear what factors influence the likelihood that a young adult smoker would participate in a formal smoking cessation program. Prior research in older adults suggests a host of factors (e.g., demographic, smoking history, social, and psychological) may contribute to nonparticipation in smoking cessation programs (8)(9)(10)(11)(12). These factors include gender, race, education, smoking rate, and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%